"I really want people to use our work to be safe"…Using participatory research to develop a safety intervention for adults with intellectual disability. (September 2020) - Hughes, Rosemary B; Robinson-Whelen, Susan; Goe, Rebecca; Schwartz, Michelle; Cesal, Lisa; Garner, Kimberly B; Arnold, Katie; Hunt, Tina; McDonald, Katherine E
People with intellectual disability experience disproportionately high rates of interpersonal violence (IPV) due, in part, to disability-related risks that often can be minimized through targeted intervention. In this article, we describe using an academic and community participatory research approach to develop and test the feasibility of an accessible IPV prevention program for people with intellectual disability. The Safety Class, which is an interactive, structured, eight-session, weekly face-to-face group program, was found feasible for implementation in an efficacy study. Working in partnership with the intellectual disability community through all phases of the project helps ensure the relevance, inclusion, and accessibility of The Safety Class .